Private Enforcement no mercado de capitais - Luz, Emylha Marya Vieira Domingos (2020)
One of the biggest problems faced by partners, shareholders, companies and third interested parties in the Capital Market is the pursuit of their civil rights in situations of market crimes committed by the company's administrators and majority shareholders. The present paper will analyze the obstacles faced in the pursuit of compensation for damages, drawing a parallel with the system of private law enforcement already practiced in the United States, seeking solutions that would facilitate the filing of actions by the interested parties, without having to wait for the Regulatory Agencies and Public Prosecutors to take appropriate action